Itanong mo sa buwan - Rono, Chito ([s.l.] Double M Films International., 1988)
In the aftermath of a bank robbery in which she is taken hostage, Josie tells the police, her family and friends a scarcely credible tale. Nonetheless, as they have no alternative story, they reluctantly accept it.
DVD
Mark Gil, Anjo Yllana, Jaclyn Jose
Keywords: Feature Films